Kako gledališki sistemi vplivajo na gledališko življenje - Hoogen, Quirijn Lennert van den (Amfiteater (Ljubljana), 2015)
This article discusses the methodology and outcomes of the STEP City Study on theatre in European cities. Its aim is not only to give a general overview of the outcomes of the comparison of the theatre systems of seven smaller cities, the supply of theatre and the use that it is made of it and the types of experiences theatre generates, but also to draw some general conclusions regarding the impact of the different theatre systems in these seven countries. Logically, in comparative research one focuses on the different outcomes of different systems and explanations behind them, though they cannot be but tentative, given the current state of the research. We discuss two distinctions specifically: between Eastern and Western European cities and between touring and residential theatre systems. However, the similarities between the outcomes of the theatre systems of these seven cities are also striking and should be acknowledged.
Keywords: Europe; Evropa; experience of theatre; gledališče; gledališka ponudba; gledališke izkušnje; gledališki sistemi; international comparative theatre survey; mednarodne primerjave; občinstvo; residential system; STEP; theater; theatre supply; theatre systems; touring system